Prevalence, ocular associations and perioperative surgical complications of pseudoexfoliation syndrome in patients scheduled for cataract surgery - Ahmed F Gabr; Hisham Z Shaban; Mohammad Z Ibrahim; Animish H Mistry (Journal of the Egyptian Ophthalmological Society, 2015)
Purpose The aim of this work was to study the prevalence, possible ocular association, and perioperative surgical complications of pseudoexfoliation syndrome (PXF) in patients with age-related cataract scheduled for surgery in Najran district, south Saudi Arabia. Design Retrospective comparative study. Patients and methods In this retrospective comparative study, 681 consecutive patients scheduled for routine cataract surgery were included. All patients were aging 60 years old or more. Full ophthalmological examination including visual acuity, refraction, slit-lamp examination, Goldmann applanation tonometry, gonioscopy, type of cataract, and dilated-pupil fundus examination was performed. Intraoperative and early postoperative complications of surgery were reported and statistical analysis was done. Results Pseudoexfoliation was identified in eyes of 192 patients with overall incidence of 28.19%. It was found unilaterally in 46.87% and bilaterally in 53.13% of patients. The mean age for PXF group was 73.47 ± 22.36 years and 72.36 ± 21.63 years for non-PXF group. The occurrence of pseudoexfoliation was found to be significantly higher with advancement of age. Ocular hypertension and glaucoma were reported in PXF group more than in non-PXF group. Nuclear, hypermature, and cortical cataracts were found to be more frequently associated with pseudoexfoliation compared with those without pseudoexfoliation. Association of PXF with some ocular conditions as well as with perioperative complications was reported and discussed. Conclusion PXF is a common age-related disorder in patients with age-related cataract in Najran area, south Saudi Arabia with overall incidence of 28.19%. PXF was found to be associated with certain types of cataract, glaucoma, other ocular conditions as well as increased incidence of operative complications.